Pengaruh Pelayanan Akademik dan Administrasi Terhadap Kepuasan Mahasiswa Kebidanan Hafshawaty Zainul Hasan Genggong Probolinggo Jawa Timur - Lia Kholida; Putri Maharani (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2026)
The purpose of this study was to determine the effect of academic services and administrative services on the satisfaction of midwifery students at Hafhawaty Zainul Hasan Genggong Probolinggo, East Java. This study was a quantitative study with a causal research design. A sample of 150 students was obtained based on non-probability sampling using the saturated sampling method. The data analysis method used in this study was multiple linear regression analysis using Microsoft Excel 2019 and SPSS 26.0 as the analysis tools. Based on the results of the study and discussion, the researcher concluded that academic and administrative services, both partially and simultaneously, had a positive and significant effect on student satisfaction. This study was only conducted by the Hafshawaty Zainul Hasan Genggong Midwifery Academy (Probolinggo, East Java) and did not use control variables or other variables that could affect student satisfaction. This study highlights the need for institutions to prioritize improving academic and administrative support systems so that students can have a satisfying experience during their studies.